SEASONAL VARIATION OF NITROGEN CYCLING IN MANILA BAY - Hayashi, Mitsuru; Yanagi, Tetsuo; San Diego-Mcglone, Maria Lourdes (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
Seasonal variation in nitrogen cycling at the upper layer of the Pasig River estuary in Manila Bay was calculated during January 1996 to December 1998 by using the numerical ecosystem model. Chl.a and DIN concentrations are relatively low, river discharge is small, and solar radiation is strong from March to May in dry season. The main reason of low chl.a concentration is that the solar radiation is too strong. On the other hand, as DIN concentration is relatively high and solar radiation is optimum, chl.a concentration is relatively high from August to December in rainy season. Main source of DIN in rainy season is the vertical transport from the lower layer due to the strong estuarine circulation.